Sosialisasi Dan Pendampingan Sertifikat Halal Bagi Para Pelaku Usaha UMKM Komisi Pemberdayaan Ekonomi Umat MUI Kota Tangerang Tahun 2023 - Lely Syafawi; Hani Hasanah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The aim of this activity is to provide understanding and assist in processing halal guarantee certification for MSMEs. The methods of this activity are observation, interviews and documenting selected MSME data. Mentoring activities are carried out online and offline. The results of observations and interviews with 120 food and beverage business actors from 13 sub-districts resulted in several conclusions, namely, the halal certification program is already known to all MSMEs but most are not interested for several reasons such as: 1) they still prioritize time for selling rather than following socialization about guarantees. halal, 2) processing halal certification is still complicated and confusing, 3) they don't have the funds to process the certification, 4) because they don't want to take care of guaranteeing the halalness of their products. Judging from the understanding/cognitive aspect, MSMEs feel that halal certification is very important (58%), and in the affective aspect the value is important (41%), and in the behavioral aspect the value is important/good (39%), meaning that understanding and knowledge about halal certification Good things are not enough to increase the interest of MSMEs in obtaining halal guarantee certification.